Identifying latent profiles of emotion dysregulation in a sample of primarily Black women with trauma exposure. (December 2022) - Kuzyk, Eva; Mekawi, Yara; Michopoulos, Vasiliki; Powers, Abigail
Abstract: Background: Emotion dysregulation (ED) is a heterogenous, multi-dimensional transdiagnostic risk factor relevant to the development and maintenance of both internalizing and externalizing psychopathology, especially for those who have experienced trauma. The goals of the current study were to use person-centered analyses to identify distinct profiles of individuals characterized by unique patterns of ED dimensions, and to examine differences in internalizing and externalizing symptoms in a community sample. Methods: Participants (n = 783, 97% Black, 93% women) were recruited from an urban safety net hospital with high rates of trauma exposure. Latent profile analysis was used to uncover unique patterns of ED and multinomial logistic regression to evaluate the conditional distribution of our correlates across profiles. Results: The best-fitting model uncovered four classes: Low ED (42%), Low Awareness/Clarity (34%), Low Impulse Control (17%), and High ED (6%). All classes differed in terms of internalizing symptoms (anxiety sensitivity, depression, PTSD), with classes characterized by higher ED reporting more severe symptoms. For externalizing symptoms (food addiction behaviors, alcohol and drug abuse, aggressive behavior), the Low ED class reported fewer symptoms than all other profiles, while Low Awareness/Clarity, Low Impulse Control, and High ED did not differ from each other. Conclusions: Patterns of emotion dysregulation ought to be assessed and considered as treatment targets for those experiencing both internalizing and externalizing psychopathology symptoms.